2017
DOI: 10.1080/21645515.2017.1289301
|View full text |Cite
|
Sign up to set email alerts
|

HPV vaccines: Global perspectives

Abstract: The discovery of HPV as the etiological factor for HPV-associated malignancies and disease has opened up several opportunities for prevention and therapy. Current commercially available HPV vaccines (Gardasil, Gardasil 9, and Cervarix) are prophylactic in nature and derived from adjuvanted L1-based virus-like particles of HPV. Globally, through several clinical trials, they were found to be very safe and efficacious. Certain limitations such as cost-effectiveness, low coverage against all HPV types and a 3-dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Nine-valent human papillomavirus (9vHPV) vaccine is widely used worldwide in preventing the infection of HPV16, 18,6,11,31,33,45, 52 and 58 [34]. HPV53 and 51, which were found in 6.3% of HPV infection and 8.9% of cervical cancer in Jilin province of China, are not covered by the 9vHPV vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Nine-valent human papillomavirus (9vHPV) vaccine is widely used worldwide in preventing the infection of HPV16, 18,6,11,31,33,45, 52 and 58 [34]. HPV53 and 51, which were found in 6.3% of HPV infection and 8.9% of cervical cancer in Jilin province of China, are not covered by the 9vHPV vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that the BPVL1-E7 fusion DNA design may elicit E7-specific CD8+ T cell response as well as L1-specific T cell and B cell responses as a single DNA construct holds significant translational values. While the currently available HPV-L1 VLP-based prophylactic vaccines, such as Cervarix, Gardasil, and Gardasil-9, are highly effective, their use in many developing countries are impeded by the technically demanding process and high costs associated with VLP vaccine production and the difficulty of storing and maintaining the VLP vaccines (for review see [ 31 33 ]). Kwak et al has previously suggested the potential of HPVL1 DNA vaccines to generate strong L1-specific antibody response comparable to that generated by Gardasil in vivo [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer is the fourth most common cancer globally, with 528,000 new cases annually and peak incidence in young women aged 25–34 years ( Ferlay et al, 2012 ). The HPV serotypes 16 and 18 carry a high-risk for cervical cancer ( Wang et al, 2018 ) and vaccination against these specific serotypes has been available since 2006 through bivalent (16 and 18), quadrivalent (6, 11, 16, and 18), and nonavalent (6, 11, 16, 18, 31, 33, 45, 52, 58) vaccines, which are now available to individuals from the age of 9 years ( Gupta et al, 2017 ). A vaccination program started in the United Kingdom in 2008, and at the time of writing over 10.5 million doses had been given to girls ( Public Health England, 2018 ), with the aim of preventing primary infection with HPV.…”
Section: Health Benefits Of Vaccinationmentioning
confidence: 99%